Hypoglycaemic activity of ethanolic extract of Garcinia mangostana Linn. pericarp in normoglycaemic and streptozotocyn-induced diabetic rat - Tg Zakaria, Tg Muhammad Faris Syafiq; Bakhtiar, M. Taher (2013)
Mangosteen (Garcinia mangostana Linn.) fruit hull has been proven for many years as traditional treatment for skin infection, wounds and inflammatory diseases diabetes?. The study is aimed to investigate hypoglycaemic activity of Methanolic extract of Garcinia mangostana Linn. pericarp (GME) in streptozotocin-induced (STZ) diabetic rats. Oral administration of GME at doses of 50, 100 and 200mg/kg b.w. were given to STZ-induced diabetic rats and normoglycaemic rats. The screening of blood glucose level were assessed in single-dose (acute) and multiple-dose study (sub-acute). The serum biochemical parameters and histopathological alterations were examined and compared to reference standard hypoglycamic drug, glibenclamide. The toxicity study indicated safe usage of the extract indicated by……. The result showed a significant reduction of glucose level in GME with doses of 100mg/kg (p<0.001) and 200mg/kg (p<0.05) compared to 50mg/kg. Total cholesterol, serum triglyceride, urea and creatinine were reduced in the treatment group while total protein contents were increased. Histological assessment revealed a mild regenerative activity of β-cell in diabetic rats evidence?. The experimental results indicated that GME exhibited a potent anti-hyperglycaemic activity when compared to control (significany?). Thus, it could be a potential natural source for diabetic management.